Showbusiness the road to Broadway - Tesori, Jeanine 1961-; Hankin, Richard (Liberation Entertainment, 2009)
A look at the real-life drama that goes on behind the curtains and backstage at four highprofile musicals -- Wicked, Taboo, Caroline, or change, and Avenue Q -- and the creative process, from casting calls to curtain call, that captures the heartbreak and hilarity of making it big on Broadway. Every element is explored from costume design to choreography